Precise endoballoon positioning for High‐Risk sternal re‐entry in an ascending aortic pseudoaneurysm with patent coronary grafts. Issue 12 (17th October 2022) - O'Sullivan, Katie E.; Mehta, Anand R.; Vargo, Patrick R.
Abstract: Redo cardiac surgery can present a unique set of challenges even to the experienced surgeon. Although outcomes have steadily improved in the modern era; if an intraoperative adverse event occurs, there is a 5% incidence of mortality and 19% incidence of myocardial infarction, stroke or death. Overall, the modern incidence of mortality at reoperation varies but be segregated into low and higher risk cohorts depending on the planning computed tomography imaging and risk to substernal structures on re‐entry. Patients with ascending aortic or root pseudoaneurysms represent a particularly difficult subset of high‐risk patients requiring reoperative cardiac surgery due to the danger of exsanguination and air embolization. The gold standard for management of such cases remains the use of deep hypothermic circulatory arrest (DHCA) to achieve safe re‐entry in such cases however this can result in unpredictable DHCA duration depending on the degree of pericardial adhesions. We report a case of aortic pseudoaneurysm in a patient with patent coronary grafts managed using an endoballoon precisely positioned relative to the proximal anastomoses resulting in a safe surgical re‐entry and shorter DHCA time.